An Analysis of the Effects of the Severance Payment Reform on Credit to Italian SMEs - Riccardo Calcagno; Roman Kraeussl; Chiara Monticone (Tinbergen Institute, 2008)
We study the effects of the reform of the system of severance payments (TFR) of Italian employees on the cost and the access to credit for small and medium-size enterprises (SMEs). The most direct consequence of the reform is to reduce in the long run the amount of liquid assets available to Italian firms. We argue that this reform, implemented in July 2007, will reduce the aggregate investment by SMEs in a more than proportional way, since it will restrict the access to credit for some of them (Holmstrom and Tirole, 1997). However, we also predict that the reform will not increase the cost of intermediated finance, coeteris paribus. In order to assess the effects of the reform on the investment of SMEs and on the cost of bank loans, we also estimate the future outflows of TFR funds due to the reform.
Keywords: G31; G32; G38; 330; severance indemnities; moral hazard; credit constraints; SMEs; Abfindung; Reform; Kreditgeschäft; Kreditrisiko; Moral Hazard; KMU; Bankenregulierung; Italien